The curious case of the Mesolithic Iberian dogs: An archaeogenetic study. (May 2019) - Pires, Ana Elisabete; Detry, Cleia; Chikhi, Lounes; Rasteiro, Rita; Amorim, Isabel R.; Simões, Fernanda; Matos, José; Petrucci-Fonseca, Francisco; Ollivier, Morgane; Hänni, Catherine; Cardoso, João Luis; Arias, Pablo; et al.
Abstract: We investigated the genetic composition of six Canis remains from western Iberia, directly radiocarbon dated to 7, 903–7, 570 years (cal BP). They were identified as dogs via their archaeological and depositional context, osteometry, and a high percentage of aquatic diet shared with humans. For comparison, genetic data were obtained from an additional 37 Iberian dog remains from the Neolithic to Late Antiquity, as well as two Palaeolithic and a Chalcolithic Canis identified as wolves. Previous data indicated that dog mtDNA haplogroup A (HgA) is prevalent in extant European dogs (>50%), in the Near East and Asia, but rare or absent (<10%) in European Canis older than 3, 000 years (cal BP). We found a high frequency (83%) of dog HgA in Mesolithic Iberian dog remains. This is the first report of a high frequency of dog HgA in pre-Neolithic Europe. We show that, contrary to the current view, Canis with HgA did not necessarily arrive in Europe from East-Asia. This phylogeographical difference in HgA frequency demonstrates that genetic differentiation was high prior to, or as a consequence of, domestication which may be linked with pre-Neolithic local processes for Iberian wolf domestication. Our results emphasize that knowledge of both ancient wolves' and early dogs' genetic profiles from the European periphery should improve our understanding of the evolution of the European dog. Highlights: We studied the oldest Portuguese dog remains (n = 6), dated to the Mesolithic . High frequency of dog haplogroup A is reported for pre-Neolithic Iberia. Dog haplogroup A did not necessarily arrive in Europe from the East. Pre-Neolithic local processes for an Iberian wolf domestication is suggested.